Moment of Inertia Dependence of Vertical Axis Wind Turbines in Pulsating Winds - Yutaka Hara; Koichi Hara; Tsutomu Hayashi (International Journal of Rotating Machinery)
Vertical Axis Wind Turbines (VAWTs) are unaffected by changes in wind direction, and they have a simple structure and the potential for high efficiency due to their lift driving force. However, VAWTs are affected by changes in wind speed, owing to effects originating from the moment of inertia. In this study, changes in the rotational speed of a small VAWT in pulsating wind, generated by an unsteady wind tunnel, are investigated by varying the wind cycle and amplitude parameters. It is shown that the responses observed experimentally agree with simulations based on torque characteristics obtained under steady rotational conditions. Additionally, a simple equation expressing the relationship between the rotational change width and amplitude of the pulsating wind is presented. The energy efficiency in a pulsating wind remains constant with changes in both the moment of inertia and the wind cycle; however, the energy efficiency decreases when the wind amplitude is large.